Differences in vertical jump force-time characteristics between stronger and weaker adolescent basketball players - Thomas, C.; Kyriakidou, I.; dos Santos, T.; Jones, P. A. (Sports, 2017)
The countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) are commonly used to compare one`s force capacity during dynamic and isometric assessments, respectively. However, little research has investigated the influence of maximum isometric strength on drop-jump (DJ) performance. Therefore, the purpose of this study was to explore differences in CMJ and DJ force-time characteristics between stronger and weaker adolescent male basketball players. Sixteen adolescent male basketball players performed the IMTP to assess measures of peak force (IMTP PF), whereas CMJ and DJ calculated a range of kinetic and kinematic variables. Peak concentric force (CMJ-PF) in the CMJ was greater for stronger players (d = 1.99). However, no differences in DJ force-time characteristics existed between stronger and weaker players. Future research should be undertaken to investigate the role of maximum strength on DJ force-time characteristics in adolescent male basketball players. Such studies may help direct the creation of athlete training and monitoring programs more effectively to represent accurate player profiling.